ANALISIS BIAYA PELATIHAN DIGITAL MARKETING UNTUK UMKM TOKO KUE HANANIA FOOD - Monoarfa, Valentina; Panane, Sitti Annisa Y; Lawani, Sintia; Nurkamiden, Doranda Putri Farid; Sujono, Adinda I (Innovative: Journal Of Social Science Research, 2025)
This study analyzes employee training strategies at Hanania Food, particularly in improving communication skills and product packaging. The research employs a qualitative method with a direct interview approach with the business owner. The results indicate that training at Hanania Food is conducted informally over one to three days without a structured evaluation system. While this training allows employees to adapt quickly, its limitations can lead to inconsistencies in product quality and service. Compared to more structured training, informal methods are less effective in maintaining long-term work standards. Additionally, the main challenges in human resource management include the lack of an incentive system, the risk of job monotony, and difficulties in retaining employee loyalty. Therefore, a combination of informal training and a more structured system is necessary to enhance training effectiveness and employee motivation.